The effects of work-related maternal risk factors on time to pregnancy, preterm birth and birth weight: the Generation R Study. Issue 3 (20th December 2010) - Burdorf, A; Brand, T; Jaddoe, V W; Hofman, A; Mackenbach, J P; Steegers, E A P
Abstract : Objective: To investigate the influence of maternal working conditions on fertility and pregnancy outcomes. Methods: 8880 women were enrolled in a large prospective birth cohort during early (76%), mid (21%) or late pregnancy (3%) (61% participation). Complete questionnaire information was available for 6302 women (71% response). Outcomes were prolonged time to pregnancy (TTP) (>6 months), preterm birth (<37 weeks) and decreased birth weight (<3000 g). Self-reported exposure to chemical agents was based on a limited list of chemicals. Physical load questions concerned manual materials handling, prolonged sitting and long periods of standing. A job-exposure matrix (JEM) linked reported job title to workplace chemical exposure within jobs according to expert judgement. Associations between maternal occupational exposure and fertility and pregnancy outcomes, adjusted for age, education, minority, parity, smoking and alcohol use, were studied using logistic regression analysis. Results: Women in jobs with regular handling of loads ≥5 kg had better fertility and pregnancy outcomes. No self-reported exposure to chemicals was associated with any outcomes and self-assessments had very low reliability compared with JEM-based assessments. JEM-based maternal occupational exposure to phthalates was associated with prolonged TTP (OR 2.16, 95% CI 1.02 to 4.57) and exposure to pesticides was associated with decreased birth weight (OR 2.42, 95% CI 1.10 to 5.34). The population attributable fractions were small at 0.7% for phthalates and 0.7% for pesticides. Conclusion: This birth cohort study presents evidence of health-based selection into the workforce and adverse effects of maternal occupational exposure to phthalates and pesticides on fertility and pregnancy outcomes.